Diagnostics of knee joint dysplasia - V. M. Shimon; I. I. Pushkash (Zaporožskij Medicinskij Žurnal)
Dysplasia of the knee is a severe congenital disorder of locomotor system, which is an extremely complex medical and social problem in orthopedics. Diagnosis of dysplasia of the knee is one of the most urgent problems of orthopedics, the percentage of such patients is 70-80%. Frontal deformation and deformation in the sagittal plane is a component of knee dysplasia.